1998
DOI: 10.1097/00007632-199810150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Pseudarthrosis in the Osteoporotic Spine

Abstract: The unstable cleft in the affected vertebral body of the osteoporotic spine with magnetic resonance findings of low intensity on the T1-weighted scans and high intensity on the T2-weighted scans suggests that the cleft is a false joint lined by fibrocartilaginous tissue with notable movement consistent with pseudarthrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 15 publications
2
89
1
2
Order By: Relevance
“…In the present study, we found that IVC (10 recompressions out of 24 IVCs) was one of the factors most strongly related to recompression. IVC provides radiological evidence of osteonecrosis [5,19,22,24,27], or nonunion and pseudoarthrosis after vertebral fracture [1,2,11,13,23]. Whatever the reasons, IVC might be made in chronic period of fracture healing process after initial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that IVC (10 recompressions out of 24 IVCs) was one of the factors most strongly related to recompression. IVC provides radiological evidence of osteonecrosis [5,19,22,24,27], or nonunion and pseudoarthrosis after vertebral fracture [1,2,11,13,23]. Whatever the reasons, IVC might be made in chronic period of fracture healing process after initial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Ettinger et al reported that vertebral deformities cause marked back pain if vertebral height ratios fall four standard deviations below the normal mean [6]. However, pseudoarthrosis following OVF has recently come to be considered a poor prognostic factor for prolonged and intractable pain [10,14,16]. On the other hand, Hashidate et al reported that in 66.7% of patients back pain decreased naturally despite the presence of vertebral instability in cases of vertebral pseudoarthrosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…Vertebral pseudarthrosis is a relatively rare, painful condition associated with osteoporotic vertebral fractures [1][2][3][4]. To date, controversies still prevail regarding terminology, pathogenesis, and treatment of this condition.…”
Section: Introductionmentioning
confidence: 99%